The Use Of Water- And Pocket-Pulse Amplitude Modulation In Investigating Photophysiology And Nutrient Limitations In Microalgae - Darif, Nur Aqilah Muhamad (2018)
Investigating photosynthesis and nutrient limitations of microalgae allow for insight into how cells will respond to different environmental or physical stressors particularly nutrients. Advances in chlorophyll fluorescence techniques have provided a means for rapid and non-invasive measurement of microalgal ecophysiology. Furthermore, available Pulse Amplitude Modulation (PAM) fluorometers in the market present different technical characteristics and configuration which may lead to different photosynthetic parameters output. Here the photosynthetic activities of microalgae were observed using both Water-PAM and Pocket-PAM to validate the differences between these two fluorometers.